Evaluation of homemade fermented pickle juice as a marinade: Effects on the microstructure, microbiological, physicochemical, textural properties, and sensory attributes of beef strip loin steaks - Incili, Canan Akdeniz; Karatepe, Pinar; Akgol, Muzeyyen; Tekin, Ali; Incili, Gokhan Kursad; Hayaloglu, Ali Adnan (Elsevier Sci Ltd, 2023)
The current study aimed to characterize homemade fermented pickle juice and evaluate its efficacy as a marinade on physicochemical, microbiological, textural properties, microstructure, and sensory attributes of the strip loins. Organic acids, phenolics, flavonoids, volatiles, total phenolic content (TPC), and in-vitro antioxidant capacity (ABTS and FRAP) analyses were carried out. Furthermore, minimum inhibitory concentration (MIC), and the diameter of inhibition zones of the pickle juice were determined against Escherichia coli O157:H7, Salmonella Typhimurium, S. enteritidis, and Listeria monocytogenes. The strip loins were marinated with five different concentrations (10%, 25%, 50%, 75%, and 100%) of pickle juice at 4 degrees C for 24 h. A total of 4 organic acids, 23 phenolic and flavonoid compounds, and 69 volatiles were identified in the pickle juice. The TPC, ABTS, and FRAP values of the pickle juice were found to be 184.24 +/- 33.28 GAE/L, 44.48 +/- 0.41 mg TEAC/L, and 2.79 +/- 0.01 mM FE/L, respectively. The MIC and inhibition zones were recorded between 7.81 and 12.50% and 8.25-13.80 mm against pathogenic bacteria, respectively. The textural properties of the strip loins marinated with 100% pickle were improved compared to the control (P < 0.05). Moreover, this concentration decreased the number of pathogens in strip loins, ranging between 1.07 and 2.77 log(10) CFU/g (P < 0.05). Regarding sensory attributes, the strip loins marinated with 50% and 100% pickle juice had higher scores compared to the non-marinated samples. The results of this study indicated that pickle juice can be evaluated as a marinade to improve the microbiological quality and textural properties of strip loins.
Keywords: Pickle juice; Marination; Strip loin; Microbiological quality; Texture